Faktor yang Mempengaruhi Kinerja Perangkat Desa - Murtadho, Sub'khan; Dian Anita Sari (Jurnal Manajemen Bisnis Digital Terkini, 2025)
This research aims to prove the influence of work ability, motivation and work stress on the performance of village officials throughout Kaliori District. The population in this study was village officials throughout Kaliori District using a saturated sample, namely a total of 167 respondents. The data analysis technique uses multiple linear regression analysis. The results of this research show that partially work ability and motivation have a positive effect and work stress has a negative effect, all of which are significant on the performance of village officials throughout Kaliori District. The Adjusted R Square value is 0.734, as is the variability of the dependent variable, namely employee performance, which can be explained by independent variables which include work ability, motivation and work stress, amounting to 73.4%, while 26.6% is explained by variations in other variables not explained in this research.